Undergraduate Education during Pandemic times Versus the (Mis) orientation of Official Documents (Research, Society and Development, 2020)
The world has been experiencing great challenges due to the Covid-19 pandemic since the beginning of 2020. Since March, the disease caused a series of changes in the educational scenario, when classes were suspended in Brazil. From this on, there has been the publication of documents to establish guidelines for the educational institutions, presenting generic terms with little orientation to responsible personnel and to pedagogical work. Therefore, the aim of this paper is to problematize and reflect over the orientations from two federal public Universities in regard of coronavirus pandemic in Brazil. In order to do this, documents related to education given by referred IES during the pandemic have been analyzed. We would like to highlight that there have been challenges regarding public educational policies, which promote strategic actions to deal with the pandemic, in all documents used.